Pengaruh Model Radec Terhadap Keterampilan Berpikir Kritis Siswa Pada Pembelajaran IPS Materi Keragaman Budaya Kelas IV SD - Insani, Galuh Nur; Rustini, Tin; Nurjaman, Asep Rudi (Universitas Hamzanwadi, 2025)
Abstract This study aims to explore the effect of the RADEC learning model on improving students' critical thinking skills in learning Social Sciences (IPS), especially cultural diversity material. The method used is a quantitative approach with a quasi-experimental research design and Non-equivalent Control Group Design. This study involved two groups, namely the experimental class using the RADEC learning model and the control class using the Problem-Based Learning (PBL) model. Data were obtained through pre-test and post-test, and analysis using IBM SPSS Statistics 25. The results showed that the RADEC learning model had a significant positive effect on improving students' critical thinking skills. In the experimental class, the average pre-test score was 65.85, while the post-test increased to 88.00, with the t-test producing a significance value of 0.000 (<0.05), indicating a significant difference. In addition, the N-Gain analysis showed an average increase of 0.63 in the experimental class and 0.46 in the control class, indicating a greater impact on the experimental class. Therefore, the RADEC model is proven to be more effective in improving critical thinking skills compared to the PBL model, so it can be a relevant alternative for developing high-level thinking skills in elementary school students.